2000
DOI: 10.1248/cpb.48.694
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antifungal Activities of R-102557 and Related Dioxane-Triazole Derivatives.

Abstract: Novel triazole compounds with a dioxane ring were synthesized. Condensation of the diol precursor 10 with various aromatic aldehydes 11-13 under acidic conditions afforded a series of dioxane-triazole compounds 14-16. The antifungal activities of the compounds 14-16 were evaluated in vivo in mice infection models against Candida and Aspergillus species. High activities were seen for the derivatives with one or two double bond(s) and an aromatic ring substituted with an electron-withdrawing group in the side ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…New 1,2,4-triazoles (2) having a difluoro(substituted sulfonyl)methyl moiety were designed and synthesized via key intermediates (3). The introduction of fluorine atoms into the triazole antifungals enhanced their antifungal activities in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…New 1,2,4-triazoles (2) having a difluoro(substituted sulfonyl)methyl moiety were designed and synthesized via key intermediates (3). The introduction of fluorine atoms into the triazole antifungals enhanced their antifungal activities in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10] There have been some efforts to overcome this problem by using a prodrug approach. [11][12][13][14] Previously, we identified CS-758 [15][16][17] which has a broad antifungal spectrum covering Aspergillus spp., FLCZ-resistant Candida spp. and has a good safety profile, including low drug-drug interaction.…”
mentioning
confidence: 99%
“…1) From such compounds, R-102557 (3d) was chosen as a candidate compound for development on the basis of its in vivo activities in mice. Since it was found that R-102557's high in vivo activities were caused by its excessively long elimination half-life in plasma, 2) we determined to search for a similar compound but with a shorter half-life.…”
mentioning
confidence: 99%
“…We reasoned that, even if a compound with good MICs were to exhibit only fair in vivo activities in mice, the compound might still be able to remain sufficiently long in humans to exhibit reasonable therapeutic effects. On this assumption, some of the previous compounds, such as 3b-g, 1) were re-evaluated on the basis of MICs. Their precursor 1a was also submitted for MIC determination.…”
mentioning
confidence: 99%
See 1 more Smart Citation